High-rate long-cycle sodium ion positive electrode material and preparation method thereof
By doping elements into the core material of sodium ion battery material and forming a composite cladding layer, the problem of phase change in the material during charging and discharging is solved, and the magnification and cycling performance of the material are improved.
Patent Information
- Application Number
- CN202510032674.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing NaxNiaFebMncO2 battery materials are prone to phase change during charging and discharging, resulting in negative impact on the specific capacity and rate performance of the material.
The sodium ion positive electrode material adopts a core-shell structure, by doping Ca or K in the core material to occupy the sodium position and Zr, Al, Sn, Sb, Mg, Ti, W, Y, and La in the metal position, and forming a composite cladding layer of NaCoO2 and Co3O4 on the surface, stabilizes the crystal structure of the material and improves electrical performance.
It effectively reduces the structural variation of the material during the circulation process, provides a good vacancy channel for the disengagement and embedding of sodium ions, maintains the rate performance of the material and improves the circulation performance.
Smart Images

Figure CN119833609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery positive electrode materials, and in particular to a high-rate and long-cycle sodium ion positive electrode material and a preparation method thereof. Background Art
[0002] Sodium ion batteries have a higher positive electrode redox potential, which can improve the overall energy density of the battery; they are highly stable in the electrolyte and have a stable structure during charging and discharging; they have high electronic conductivity and ionic conductivity, and are simple to prepare, environmentally friendly, safe and non-toxic.
[0003] Na x Ni a Fe b Mn c Although O2 battery materials have good advantages in capacity, cycle performance, energy density and other properties, battery materials are prone to phase change during the charging and discharging process, and the specific capacity and rate performance of the materials are seriously negatively affected. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-rate and long-cycle sodium ion positive electrode material and a preparation method thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a high-rate long-cycle sodium ion positive electrode material, the high-rate long-cycle sodium ion positive electrode material is a core-shell structure, including a core material located inside and a coating layer coated on the surface of the core material, and the chemical formula of the high-rate long-cycle sodium ion positive electrode material is (Na x M1 y )Ni a Fe b Mn c M2 d O2@M, @M represents a coating layer coated on the surface of the core material, M is a mixture of NaCoO2 and Co3O4, and the coating layer accounts for 0.3% to 1.2% of the mass of the high-rate and long-cycle sodium-ion positive electrode material, wherein 0.8≤x+y≤1.05, 0.1≤a≤0.6, 0.1≤b≤0.5, 0.1≤c≤0.5, and a+b+c+d=1, 0.01≤d≤0.1, M1 is at least one of Ca or K, and M2 is at least one of Zr, Al, Sn, Sb, Mg, Ti, W, Y, and La.
[0006] The high-rate and long-cycle sodium ion positive electrode material is a core-shell structure. In the core material inside, Ca or K is doped at the sodium position to occupy the sodium ion position, and Zr, Al, Sn, Sb, Mg, Ti, W, Y, and La are doped at the metal position to occupy the nickel, iron, and manganese positions, which can stabilize the crystal structure of the material. In particular, during the phase change in the charge and discharge process, the synergistic doping of the sodium position / metal position effectively supports the crystal, reduces the structural mutation of the material during the cycle, and provides a good vacancy channel for the escape and embedding of sodium ions, which can not only maintain the rate performance of the material, but also improve the cycle performance of the material; NaCoO2 and Co3O4 composition The mixture is coated on the internal core material to form a coating layer. During the charge and discharge process, the O3 phase of NaCoO2 undergoes an O3-O′3-P′3-P3-P′3 phase transition. P3-P′3 has a faster Na ion diffusion pathway, which is beneficial to further improve the material rate performance. Co3O4 is a stable inorganic compound that can prevent the electrolyte from further corroding the material surface, reduce the side reactions that occur during the charge and discharge process, and is beneficial to improve the cycle performance. The composite coating layer of NaCoO2 and Co3O4, the synergistic effect of the two, can improve the material's rate performance and cycle performance, and better improve the material's electrical properties. The above-mentioned high-rate and long-cycle sodium ion positive electrode material combines the doping of the internal core material sodium site and the metal site with the composite coating of NaCoO2 and Co3O4 on the surface of the core material, which synergistically improves the material's rate performance and cycle performance.
[0007] Preferably, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:(0.3-1.7).
[0008] Preferably, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:(0.6-1.0).
[0009] In the above-mentioned high-rate and long-cycle sodium ion positive electrode material, the composite coating of NaCoO2 and Co3O4 can prepare sodium ion positive electrode materials (Na2O2 / Co3O4) with different mass ratios of NaCoO2 and Co3O4 in the coating layer by adjusting the sintering temperature and time of the coating layer during the sintering process. x M1 y )Ni a Fe b Mn c M2 dO2@M, the inventors found that the mass ratio of NaCoO2 to Co3O4 has an impact on further improving the rate performance and cycle performance of the material, and when the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1: (0.6-1.0), the rate performance and cycle performance of the sodium ion positive electrode material can be better improved. The present invention controls the ratio of the surface coating by controlling the atmosphere and the sintering temperature during the sintering stage to form a composite coating layer that meets the above ratio.
[0010] Preferably, the coating layer accounts for 0.5% to 1.0% of the mass of the high-rate and long-cycle sodium-ion positive electrode material.
[0011] In the above-mentioned high-rate long-cycle sodium ion positive electrode material, when the coating layer accounts for 0.5% to 1.0% of the mass of the high-rate long-cycle sodium ion positive electrode material, the sodium ion positive electrode material has better rate performance and cycle performance.
[0012] Preferably, M1 is at least one of Ca or K, and M2 is at least one of Zr, Sn, Mg, Ti, W, Y, and La.
[0013] More preferably, M1 is Ca, M2 is a combination of Zr and Mg, or M2 is a combination of Mg and Ti.
[0014] When the inventors were screening and optimizing the doping elements, they found that when NaCoO2 and Co3O4 were used as composite coating layers, Ca sodium doping was used to occupy the sodium ion position in the internal core material, and M2 was a combination of Zr and Mg, or M2 was a combination of Mg and Ti and doped at the metal position to occupy the nickel iron manganese position, which could further stabilize the crystal structure of the material and improve the battery performance of the material.
[0015] Preferably, the high-rate and long-cycle sodium ion positive electrode material is prepared by a two-step sintering method, wherein the first step is to sinter and prepare the core material (Na x M1 y )Ni a Fe b Mn c M2 d O2, the second step sintering (Na x M1 y )Ni a Fe b Mn c M2 d O2 is sintered with the raw materials of the coating layer to prepare the high-rate and long-cycle sodium ion positive electrode material.
[0016] The present invention also provides a method for preparing any of the above-mentioned high-rate and long-cycle sodium ion positive electrode materials, the method comprising the following steps:
[0017] (1) The nickel-iron-manganese raw material, the M1 compound, the M2 compound and the sodium source are uniformly mixed and sintered in an oxygen-containing atmosphere at 900°C to 1100°C to obtain the core material (Na x M1 y )Ni a Fe b Mn c M2 d O2;
[0018] (2) The (Na2O3) obtained in step (1) as the core material x M1 y )Ni a Fe b Mn c M2 d O2 and a cobalt source are mixed in deionized water and the pH of the mixed solution is adjusted to 7.0-8.5. The solid particles are collected, dried, and then sintered in an oxygen-containing atmosphere at 500° C.-800° C. for 5-8 hours.
[0019] The preparation method of the high-rate and long-cycle sodium ion positive electrode material is prepared by two-step sintering. x M1 y )Ni a Fe b Mn c M2 d O2 and cobalt source were mixed in deionized water and the pH of the mixture was adjusted to 7.0-8.5 for wet treatment. x M1 y )Ni a Fe b Mn c M2 d Some residual sodium carbonate and residual sodium hydroxide on the surface of O2 will dissolve into the water. At the same time, after the coating is heat treated, the residual sodium content on the surface is very low, it has good air stability, and the product has excellent processing performance.
[0020] Preferably, the sintering time in step (1) is 10 to 20 hours.
[0021] Preferably, the sodium source is one or two of sodium hydroxide, sodium carbonate or sodium bicarbonate; the cobalt source is at least one of cobalt nitrate, cobalt chloride and cobalt sulfate; the M1 compound is the oxide, hydroxide or oxyacid salt corresponding to the element, and the M2 compound is the oxide, hydroxide or oxyacid salt corresponding to the element.
[0022] Preferably, it is characterized in that, in step (2), the core material (Na x M1 y )Ni a Fe b Mnc M2 d The weight ratio of O2 to deionized water is (1-3):1.
[0023] The beneficial effects of the present invention are as follows: the present invention provides a high-rate long-cycle sodium ion positive electrode material and a preparation method thereof. The high-rate long-cycle sodium ion positive electrode material of the present invention is a core-shell structure. In the internal core material, Ca or K is doped at the sodium position to occupy the sodium ion position, and Zr, Al, Sn, Sb, Mg, Ti, W, Y, and La are doped at the metal position to occupy the nickel-iron-manganese position, so that the crystal structure of the material can be stabilized, especially in the phase change during the charge and discharge process, the synergistic doping of the sodium position / metal position effectively supports the crystal, reduces the structural mutation of the material during the cycle process, and provides a good vacancy channel for the escape and embedding of sodium ions, which can not only maintain the rate performance of the material, but also improve the material The material has a cyclic performance; the mixture of NaCoO2 and Co3O4 covers the internal core material to form a coating layer. During the charge and discharge process, the O3 phase of NaCoO2 undergoes an O3-O′3-P′3-P3-P′3 phase transition. P3-P′3 has a faster Na ion diffusion pathway, which is beneficial to further improve the material rate performance. Co3O4 is a stable inorganic compound that can prevent the electrolyte from further corroding the material surface and reduce the side reactions that occur during the charge and discharge process, which is beneficial to improve the cycle performance. The composite coating layer of NaCoO2 and Co3O4, the synergistic effect of the two, can improve the material's rate performance and cycle performance, and better improve the material's electrical properties. The above-mentioned high-rate and long-cycle sodium ion positive electrode material combines the doping of the internal core material sodium site and the metal site with the composite coating of NaCoO2 and Co3O4 on the surface of the core material, which synergistically improves the material's rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD diagrams of the sodium ion positive electrode material of Example 1 of the present invention and the sodium ion positive electrode material of Comparative Example 1 are shown.
[0025] Figure 2 This is a SEM image of the sodium ion positive electrode material of Example 1 of the present invention.
[0026] Figure 3 This is a cycle retention rate diagram of the sodium ion positive electrode materials of Examples 1, 5, and 12 of the present invention and the sodium ion positive electrode materials of Comparative Examples 1, 2, 3, 4, and 5.
[0027] Figure 4 This is the X-ray photoelectron spectrum (XPS) of the sodium ion positive electrode material obtained in Example 1 of the present invention.
[0028] Figure 5This is a transmission electron microscope analysis image (TEM) of the sodium ion positive electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0030] Example 1
[0031] As a high-rate long-cycle sodium ion positive electrode material of an embodiment of the present invention, the high-rate long-cycle sodium ion positive electrode material is a core-shell structure, including a core material located inside and a coating layer coated on the surface of the core material. The chemical formula of the high-rate long-cycle sodium ion positive electrode material is (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 O2@M, @M represents the coating layer coated on the surface of the core material, and M is a mixture of NaCoO2 and Co3O4.
[0032] The preparation method of the high-rate and long-cycle sodium ion positive electrode material of this embodiment comprises the following steps:
[0033] (1) Sodium carbonate, calcium carbonate, nickel iron manganese precursor Ni 0.35 Fe 0.3 Mn 0.35 (OH)2, zirconium oxide are added in proportion according to the molar ratio of Na:Ca:Ni:Fe:Mn:Zr=0.95:0.05:0.3465:0.297:0.3465:0.01, preliminarily mixed in a ziplock bag and added to a high-speed mixer, first stirred at a low speed of 15Hz for 5min, then stirred at a high speed of 50Hz for 30min. After the mixing is completed, the material is placed in a calcination pot, placed in a box furnace at 1000℃ in an air atmosphere for 12h, and then naturally cooled. After coarse crushing, fine crushing and sieving, the core material (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 O2;
[0034] (2) The obtained (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01O2 core material and deionized water are added into a stirring tank at a solid-liquid ratio of 2:1 for stirring. The temperature of the solid-liquid mixture in the stirring tank is controlled at 35°C. Then cobalt nitrate is added into the stirring tank. The cobalt nitrate and (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 The weight ratio of O2 core material is 4:100. Ammonia water is used to adjust the pH value of the reaction solution to 7.8. After the addition of ammonia water is completed, the reaction is stirred for 30 minutes and then filtered. The filtered material is vacuum dried at 180°C. After the material is dried, the material is placed in a box furnace and sintered at 700°C in an air atmosphere for 6 hours. After crushing, sieving, and demagnetization, a high-rate and long-cycle sodium ion positive electrode material is obtained.
[0035] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate long-cycle sodium ion positive electrode material prepared in this embodiment, the coating layer accounts for 0.81% of the mass of the high-rate long-cycle sodium ion positive electrode material, and the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:1.01.
[0036] Example 2
[0037] As a high-rate and long-cycle sodium ion positive electrode material of the embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that the cobalt nitrate and (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 The weight ratio of O2 core material is 1:100.
[0038] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate long-cycle sodium ion positive electrode material prepared in this embodiment, the coating layer accounts for 0.36% of the mass of the high-rate long-cycle sodium ion positive electrode material, and the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:1.03.
[0039] Example 3
[0040] As a high-rate and long-cycle sodium ion positive electrode material of the embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that the cobalt nitrate and (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 The weight ratio of O2 core material is 2:100.
[0041] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate long-cycle sodium ion positive electrode material prepared in this embodiment, the coating layer accounts for 0.45% of the mass of the high-rate long-cycle sodium ion positive electrode material, and the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:1.02.
[0042] Example 4
[0043] As a high-rate and long-cycle sodium ion positive electrode material of the embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that the cobalt nitrate and (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 The weight ratio of O2 core material is 3:100.
[0044] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate long-cycle sodium ion positive electrode material prepared in this embodiment, the coating layer accounts for 0.62% of the mass of the high-rate long-cycle sodium ion positive electrode material, and the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:0.99.
[0045] Example 5
[0046] As a high-rate and long-cycle sodium ion positive electrode material of the embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that the cobalt nitrate and (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 The weight ratio of O2 core material is 5:100.
[0047] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate long-cycle sodium ion positive electrode material prepared in this embodiment, the coating layer accounts for 0.98% of the mass of the high-rate long-cycle sodium ion positive electrode material, and the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:1.02.
[0048] Example 6
[0049] As a high-rate and long-cycle sodium ion positive electrode material in an embodiment of the present invention, the only difference between this embodiment and Example 1 is that the material is placed in a box furnace and sintered at 500°C in an air atmosphere for 7 hours, and then crushed, sieved, and demagnetized to obtain a high-rate and long-cycle sodium ion positive electrode material.
[0050] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate and long-cycle sodium ion positive electrode material prepared in this embodiment, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:0.38.
[0051] Example 7
[0052] As a high-rate and long-cycle sodium ion positive electrode material in an embodiment of the present invention, the only difference between this embodiment and Example 1 is that the material is placed in a box furnace and sintered at 800°C in an air atmosphere for 5 hours, and then crushed, sieved, and demagnetized to obtain a high-rate and long-cycle sodium ion positive electrode material.
[0053] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate and long-cycle sodium ion positive electrode material prepared in this embodiment, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:0.67.
[0054] Example 8
[0055] As a high-rate and long-cycle sodium ion positive electrode material in an embodiment of the present invention, the only difference between this embodiment and Example 1 is that the material is placed in a box furnace and sintered at 800°C in an air atmosphere for 6 hours, and then crushed, sieved, and demagnetized to obtain a high-rate and long-cycle sodium ion positive electrode material.
[0056] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate and long-cycle sodium ion positive electrode material prepared in this embodiment, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:0.91.
[0057] Example 9
[0058] As a high-rate and long-cycle sodium ion positive electrode material in an embodiment of the present invention, the only difference between this embodiment and Example 1 is that the material is placed in a box furnace and sintered at 650° C. in an air atmosphere for 8 hours, and then crushed, sieved, and demagnetized to obtain a high-rate and long-cycle sodium ion positive electrode material.
[0059] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate and long-cycle sodium ion positive electrode material prepared in this embodiment, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:1.69.
[0060] Example 10
[0061] As a high-rate long-cycle sodium ion positive electrode material of the embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that the chemical formula of the high-rate long-cycle sodium ion positive electrode material is (Na 0.95 Ca 0.05 )Ni 0.3325 Fe0.285 Mn 0.3325 Mg 0.02 Ti 0.03 O2@M.
[0062] Embodiment 11
[0063] As a high-rate long-cycle sodium ion positive electrode material of the embodiment of the present invention, the only difference between this embodiment and embodiment 10 is that the chemical formula of the high-rate long-cycle sodium ion positive electrode material is (Na 0.95 K 0.05 )Ni 0.3325 Fe 0.285 Mn 0.3325 Mg 0.02 Ti 0.03 O2@M.
[0064] Example 12
[0065] As a high-rate long-cycle sodium ion positive electrode material of the embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that the chemical formula of the high-rate long-cycle sodium ion positive electrode material is (Na 0.95 Ca 0.05 )Ni 0.3325 Fe 0.285 Mn 0.3325 Mg 0.02 Zr 0.03 O2@M.
[0066] Comparative Example 1
[0067] As a sodium ion positive electrode material of the comparative example of the present invention, the only difference between this comparative example and Example 1 is that it does not contain a coating layer.
[0068] The general chemical formula of the sodium ion positive electrode material is (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 O2.
[0069] The preparation method comprises the following steps with reference to Example 1:
[0070] (1) Sodium carbonate, calcium carbonate, Ni 0.35 Fe 0.3 Mn 0.35(OH)2, zirconium oxide are added in proportion according to the molar ratio of Na:Ca:Ni:Fe:Mn:Zr=0.95:0.05:0.3465:0.297:0.3465:0.01, preliminarily mixed in a ziplock bag and added to a high-speed mixer, first stirred at a low speed of 15Hz for 5min, then stirred at a high speed of 50Hz for 30min. After the mixing is completed, the material is placed in a calcination pot, placed in a box furnace at 1000℃ in an air atmosphere for 12h, and then naturally cooled. After coarse crushing, fine crushing and sieving, the core material (Na 0.95 Ca 0.05 )Ni 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 O2;
[0071] Comparative Example 2
[0072] As a sodium ion positive electrode material of the comparative example of the present invention, the only difference between this comparative example and Example 1 is that the core material is different. The chemical formula of the high-rate and long-cycle sodium ion positive electrode material is NaNi 0.3465 Fe 0.297 Mn 0.3465 Zr 0.01 O2@M.
[0073] That is, compared with Example 1, this comparative example is the same except that the sodium position is not doped with Ca.
[0074] Comparative Example 3
[0075] As a sodium ion positive electrode material of the comparative example of the present invention, the only difference between this comparative example and Example 1 is that the core material is different, the nickel iron manganese metal position is not doped, and the chemical formula of the high-rate long-cycle sodium ion positive electrode material is (Na 0.95 Ca 0.05 )Ni 0.35 Fe 0.3 Mn 0.35 O2@M, @M represents the coating layer coated on the surface of the core material, and M is a mixture of NaCoO2 and Co3O4.
[0076] Comparative Example 4
[0077] As a sodium ion positive electrode material of the comparative example of the present invention, the only difference between this comparative example and Example 1 is that the material is placed in a box furnace and sintered at 500° C. for 4 hours, and then crushed, sieved, and demagnetized to obtain a high-rate and long-cycle sodium ion positive electrode material.
[0078] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate and long-cycle sodium ion positive electrode material prepared in this embodiment, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:0.09.
[0079] Comparative Example 5
[0080] As a sodium ion positive electrode material of the comparative example of the present invention, the only difference between this comparative example and Example 1 is that the material is placed in a box furnace and sintered at 800° C. for 4 hours, and then crushed, sieved, and demagnetized to obtain a high-rate and long-cycle sodium ion positive electrode material.
[0081] After testing by X-ray photoelectron spectroscopy (XPS) method, in the high-rate and long-cycle sodium ion positive electrode material prepared in this embodiment, the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:2.1.
[0082] Experimental methods
[0083] 1. Material Characterization
[0084] Figure 1 The XRD diagrams of the sodium ion positive electrode material obtained in Example 1 and the sodium ion positive electrode material in Comparative Example 1 are both O3 type structures. Figure 2 This is the SEM image of the sodium ion positive electrode material obtained in Example 1. Figure 3 The cycle capacity retention rate diagram of the sodium ion positive electrode materials obtained in Example 1, Example 5, and Example 12 and the sodium ion positive electrode materials in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5, Figure 4 This is the X-ray photoelectron spectrum (XPS) of the sodium ion positive electrode material obtained in Example 1. Figure 5 This is a transmission electron microscope analysis (TEM) image of the sodium ion positive electrode material obtained in Example 1.
[0085] 2. Battery Performance
[0086] The prepared sodium ion positive electrode material, conductive carbon black (SP) and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 90:5:5, and the solid content was added in a ratio of 45%, wherein the concentration of PVDF glue was 8%, and the sodium ion positive electrode material coating slurry was dispersed evenly by centrifugal high-speed stirring, and evenly coated on aluminum foil by a small coating machine, and dried pole pieces were obtained after high-temperature baking at 120°C. After rolling, the pole pieces were cut into pole pieces with a diameter of 14mm, and button-type half-cells were assembled with sodium sheets as negative electrodes, ceramic fibers as diaphragms, and 1 mol / L NaPF6 (EMC+PC+FEC (2%)) solution as electrolytes, and the test voltage was 2.0-4.0V. The experimental results are shown in Table 1.
[0087] Table 1 Battery performance of sodium ion cathode materials
[0088]
[0089]
[0090] As can be seen from Table 1, in the internal core material, Ca or K is doped at the sodium position to occupy the sodium ion position, and Zr, Al, Sn, Sb, Mg, Ti, W, Y, and La are doped at the metal position to occupy the nickel, iron, and manganese positions. The internal core material is coated with a mixture of NaCoO2 and Co3O4 to form a coating layer. During the charge and discharge process, the O3 phase of NaCoO2 undergoes an O3-O′3-P′3-P3-P'3 phase transition. P3-P'3 has a faster Na ion diffusion pathway, which is beneficial to further improve the rate performance of the material. Co3O4 is a stable inorganic compound that can prevent the electrolyte from further corroding the surface of the material, reduce the side reactions that occur during the charge and discharge process, and is beneficial to improving the cycle performance. The composite coating of NaCoO2 and Co3O4, the synergistic effect of the two, can improve the rate performance and cycle performance of the material, and better improve the electrical properties of the material. The high-rate and long-cycle sodium-ion cathode material combines the doping of the sodium and metal sites of the core material inside with the composite coating of NaCoO2 and Co3O4 on the surface of the core material, which synergistically improves the rate performance and cycle performance of the material. When the mass ratio of NaCoO2 to Co3O4 in the coating layer is 1: (0.6-1.0), the rate performance and cycle performance of the sodium-ion cathode material can be better improved.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high-rate and long-cycle sodium ion positive electrode material, characterized in that: The high-rate long-cycle sodium ion positive electrode material is a core-shell structure, including a core material located inside and a coating layer coated on the surface of the core material. The chemical formula of the high-rate long-cycle sodium ion positive electrode material is (Na x M1 y )Ni a Fe b Mn c M2 d O2@M, @M represents a coating layer coated on the surface of the core material, M is a mixture of NaCoO2 and Co3O4, and the coating layer accounts for 0.3% to 1.2% of the mass of the high-rate and long-cycle sodium-ion positive electrode material, wherein 0.8≤x+y≤1.05, 0.1≤a≤0.6, 0.1≤b≤0.5, 0.1≤c≤0.5, and a+b+c+d=1, 0.01≤d≤0.1, M1 is at least one of Ca or K, and M2 is at least one of Zr, Al, Sn, Sb, Mg, Ti, W, Y, and La.
2. The high-rate and long-cycle sodium ion positive electrode material according to claim 1, characterized in that: The mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:(0.3-1.7).
3. The high-rate and long-cycle sodium ion positive electrode material according to claim 2, characterized in that: The mass ratio of NaCoO2 to Co3O4 in the coating layer is 1:(0.6-1.0).
4. The high-rate and long-cycle sodium ion positive electrode material according to claim 1, characterized in that: The coating layer accounts for 0.5% to 1.0% of the mass of the high-rate and long-cycle sodium ion positive electrode material.
5. The high-rate and long-cycle sodium ion positive electrode material according to claim 1, characterized in that: M1 is at least one of Ca and K, and M2 is at least one of Zr, Sn, Mg, Ti, W, Y, and La.
6. The high-rate and long-cycle sodium ion positive electrode material according to claim 1, characterized in that: The high-rate and long-cycle sodium ion positive electrode material is prepared by a two-step sintering method. The first step is to sinter and prepare the core material (Na x M1 y )Ni a Fe b Mn c M2 d O2, the second step sintering will (Na x M1 y )Ni a Fe b Mn c M2 d O2 is sintered with the raw materials of the coating layer to prepare the high-rate and long-cycle sodium ion positive electrode material.
7. The method for preparing a high-rate and long-cycle sodium ion positive electrode material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) The nickel-iron-manganese raw material, the M1 compound, the M2 compound and the sodium source are uniformly mixed and sintered in an oxygen-containing atmosphere at 900°C to 1100°C to obtain the core material (Na x M1 y )Ni a Fe b Mn c M2 d O2; (2) The (Na2O3) obtained in step (1) as the core material x M1 y )Ni a Fe b Mn c M2 d O2 and a cobalt source are mixed in deionized water and the pH of the mixed solution is adjusted to 7.0-8.
5. The solid particles are collected, vacuum dried, and then sintered in an oxygen-containing atmosphere at 500° C.-800° C. for 5-8 hours.
8. The method for preparing a high-rate and long-cycle sodium ion positive electrode material according to claim 7, characterized in that: The sintering time in step (1) is 10 to 20 hours.
9. The method for preparing a high-rate and long-cycle sodium ion positive electrode material according to claim 7, characterized in that: The sodium source is one or two of sodium hydroxide, sodium carbonate or sodium bicarbonate; the cobalt source is at least one of cobalt nitrate, cobalt chloride and cobalt sulfate; the M1 compound is the oxide, hydroxide or oxyacid salt corresponding to the element, and the M2 compound is the corresponding oxide, hydroxide or oxyacid salt corresponding to the element.
10. The method for preparing a high-rate and long-cycle sodium ion positive electrode material according to claim 7, characterized in that: In step (2), as the core material (Na x M1 y )Ni a Fe b Mn c M2 d The weight ratio of O2 to deionized water is (1-3):1.
Citation Information
Patent Citations
Coated modified sodium ion layered positive electrode material and preparation method thereof
CN116314704A
Sodium ion positive electrode material and preparation method thereof
CN117059761A
Battery positive electrode material and sodium ion battery containing same
CN117080537A
Positive electrode material, preparation method thereof and battery
CN118039874A
Sodium cobaltate coated lithium cobaltate composite material as well as preparation method and application thereof
CN118431438A
Cited By
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN120998989A